BC / MXene-coated MoS2 composite aerogel as well as preparation method and application thereof
By using BC/MXene@MoS2 composite aerogel in microwave absorption materials, the mechanical properties and frozen casting process are enhanced by bacterial cellulose, and the MoS2 nanosheets are grown through hydrothermal reaction, the absorption of traditional materials in electromagnetic wave pollution is solved. The problem of insufficient performance achieves efficient electromagnetic wave absorption effect.
Patent Information
- Application Number
- CN202411648496.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional microwave absorbing materials have problems such as high density, narrow absorption bandwidth and poor impedance matching in electromagnetic wave pollution, which leads to limitations in their applications.
BC/MXene@MoS2 composite aerogel was used to enhance the mechanical properties through bacterial cellulose and micron-scale orientation pores were constructed through frozen casting-freeze-drying technology, and the MoS2 nanosheets were grown in combination with hydrothermal reaction to improve impedance matching.
It has achieved efficient absorption of electromagnetic waves under low density and low filling conditions, with an absorption bandwidth of 7.04GHz, covering the Ku band and some X bands, meeting the application needs of lightweight, thin thickness, strong absorption and wide bandwidth.
Smart Images

Figure CN119161641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a BC / MXene@MoS2 composite aerogel and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of information technology, especially the advent of the fifth generation (5G), it has brought great convenience to people's lives. High-power electronic devices including satellite communications, broadband radars, wireless networks and portable digital hardware are increasingly used in human health, information security and national defense security. However, while technology has changed our lives, it has also brought serious electromagnetic wave pollution, which can destroy the normal functions of electronic devices and pose a potential threat to human health. In order to solve this problem, the development of lightweight, thin, strong absorption and wide bandwidth microwave absorbing materials (MAMs) has become a research hotspot in recent years.
[0003] Traditional MAMs, such as carbon black, ferrites, and magnetic metals, have achieved good electromagnetic wave (EMW) performance, but these materials have disadvantages such as high density, narrow absorption bandwidth, and high filling ratio. Compared with traditional MAMs, MXene-based aerogels have a unique three-dimensional network structure and high specific surface area and low density, and can obtain excellent wave absorption performance at low filling amount. However, the application of MXene aerogel alone is greatly limited due to its poor mechanical properties. In addition, due to its excellent electrical conductivity, MXene leads to poor impedance matching of aerogels, causing most of the electromagnetic waves to be reflected on the surface of the material, making it difficult to enter the absorbing material. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a BC / MXene@MoS2 composite aerogel and a preparation method and application thereof. The present invention uses bacterial cellulose as a binder to enhance the mechanical properties, obtains BC / MXene aerogel by freeze casting-freeze drying, and then grows MoS2 nanosheets on the surface of the aerogel by hydrothermal synthesis to improve the impedance matching of the material, and finally obtains BC / MXene@MoS2 microwave absorbing material, which provides a new idea for solving the problem of electromagnetic wave pollution.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a BC / MXene@MoS2 composite aerogel, comprising a BC / MXene skeleton and MoS2 nanosheets loaded on the BC / MXene skeleton.
[0006] The present invention also provides a method for preparing the BC / MXene@MoS2 composite aerogel described in the above technical solution, comprising the following steps: 1) Mixing the monolayer MXene powder with the bacterial cellulose dispersion to obtain a precursor dispersion; 2) freeze-casting the precursor dispersion obtained in step 1), and freeze-drying to obtain BC / MXene aerogel; 3) ammonium molybdate tetrahydrate, thiourea and water are mixed to obtain a mixed solution, and the BC / MXene aerogel obtained in the step 2) is immersed in the mixed solution to obtain a BC / MXene@MoS2 composite aerogel after a hydrothermal reaction.
[0007] Preferably, in step 1), the mass ratio of the monolayer MXene powder to the bacterial cellulose dispersion is 0.06-0.08:10; The mass percentage of the bacterial cellulose dispersion is 0.8%; The mixing is performed under stirring, and the stirring conditions include: a rotation speed of 1300 rpm and a time of 5 hours.
[0008] Preferably, the conditions of freeze casting in step 2) include: temperature of -80 to -196°C and time of 1 hour; The freeze-drying conditions include: temperature of -55°C and time of 48h.
[0009] Preferably, in the step 2), the precursor dispersion is freeze-casted in a directional freeze-casting mold, and the directional freeze-casting mold comprises a copper base and an acrylic square tube. The size of the copper base is 60×60×2mm, the wall thickness of the acrylic square tube is 5mm, and the inner cavity size is 20×20×25mm.
[0010] Preferably, in step 3), the mass ratio of ammonium molybdate tetrahydrate, thiourea and water is 1.0595:2.2835:30; The ratio of the volume of the mixed liquid to the number of BC / MXene aerogels is 30 mL:1.
[0011] Preferably, the soaking time in step 3) is 12 hours; The conditions of the hydrothermal reaction include: temperature of 200° C. and time of 18 to 24 hours.
[0012] The present invention also provides the use of the BC / MXene@MoS2 composite aerogel described in the above technical solution in the preparation of electromagnetic wave absorbing materials.
[0013] The present invention also provides the use of the BC / MXene@MoS2 composite aerogel described in the above technical solution in improving the wave absorbing performance of electromagnetic wave absorbing materials.
[0014] The present invention also provides the application of the BC / MXene@MoS2 composite aerogel described in the above technical solution in improving the impedance matching of electromagnetic wave absorbing materials.
[0015] Beneficial effects of the present invention: (1) The present invention utilizes biomass materials, the raw materials are easily available, the production cost is low, and the materials have excellent mechanical properties, which can effectively improve the mechanical properties of aerogels. In addition, bacterial cellulose is also a low dielectric material, which can improve the impedance matching problem (the material has a wide absorption performance and absorption bandwidth, indicating that the material has good impedance matching at the absorption frequency); (2) The present invention successfully constructs micron-scale directional channels inside the material by means of freeze casting-freeze drying process, and the structure has strong controllability, which helps to achieve multi-scale regulation of the electromagnetic properties and wave absorption performance of the material; the present invention increases the specific surface area and increases the heterogeneous interface by constructing a multi-aerogel, thereby improving the interface polarization; and constructs a large number of micropores, which promotes the reflection and multiple reflection of electromagnetic waves inside the material, increases the transmission path of electromagnetic waves, and is more conducive to the material's absorption of electromagnetic waves; (3) The BC / MXene@MoS2 composite aerogel prepared in the present invention has a low density (51.2 mg / cm 3 ), and low filling (≤5wt%), the minimum reflection loss is up to 52dB (thickness is 2.62mm), and the effective absorption bandwidth is up to 7.04GHz (thickness is 2.55mm), covering the entire Ku band and part of the X band. Overall, this absorbing material is very consistent with the current application requirements of the development of new microwave absorbing materials with lightweight, thin thickness, strong absorption and wide bandwidth. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.
[0017] Figure 1 This is the XRD spectrum of the BC / MXene@MoS2 composite aerogel microwave absorbing material in Example 1; Figure 2 This is the SEM image of the BC / MXene@MoS2 composite aerogel microwave absorbing material in Example 1; Figure 3 This is the reflection loss curve of the BC / MXene@MoS2 composite aerogel microwave absorbing material at different thicknesses in Example 1; Figure 4 These are the reflection loss curves of the BC / MXene@MoS2 composite aerogel microwave absorbing materials prepared in Example 1, Example 2, Example 3 and Example 4. DETAILED DESCRIPTION
[0018] The present invention provides a BC / MXene@MoS2 composite aerogel, comprising a BC / MXene skeleton and MoS2 nanosheets loaded on the BC / MXene skeleton.
[0019] The present invention provides a method for preparing the BC / MXene@MoS2 composite aerogel described in the above technical solution, comprising the following steps: 1) Mixing the monolayer MXene powder with the bacterial cellulose dispersion to obtain a precursor dispersion; 2) freeze-casting the precursor dispersion obtained in step 1), and freeze-drying to obtain BC / MXene aerogel; 3) ammonium molybdate tetrahydrate, thiourea and water are mixed to obtain a mixed solution, and the BC / MXene aerogel obtained in the step 2) is immersed in the mixed solution to obtain a BC / MXene@MoS2 composite aerogel after a hydrothermal reaction.
[0020] The present invention mixes a monolayer MXene powder with a bacterial cellulose dispersion to obtain a precursor dispersion. The present invention does not specifically limit the sources of the monolayer MXene powder and bacterial cellulose, and conventional commercially available products can be used. For example, bacterial cellulose is purchased from Guilin Qihong Technology Co., Ltd., product model: bacterial cellulose dispersion (solid content: 0.8%wt) diameter 50-100nm. In the present invention, the mass ratio of the monolayer MXene powder to the bacterial cellulose dispersion is preferably 0.06~0.08:10. In the present invention, the mass percentage of the bacterial cellulose dispersion is preferably 0.8%. In the present invention, the mixing is preferably carried out under stirring, and the stirring conditions preferably include: a rotation speed of 1300rpm and a time of 5h.
[0021] The present invention freeze-casts the obtained precursor dispersion, and obtains BC / MXene aerogel after freeze drying. In the present invention, the freeze-casting conditions preferably include: a temperature of -80~-196°C and a time of 1h. In the present invention, the freeze-drying conditions preferably include: a temperature of -55°C and a time of 48h. In the present invention, the precursor dispersion is preferably freeze-cast in a directional freeze-casting mold, and the directional freeze-casting mold includes a copper base and an acrylic square tube. The size of the copper base is 60×60×2mm, the wall thickness of the acrylic square tube is 5mm, and the inner cavity size is 20×20×25mm.
[0022] The present invention mixes ammonium molybdate tetrahydrate, thiourea and water to obtain a mixed solution, and immerses the obtained BC / MXene aerogel in the mixed solution. After hydrothermal reaction, BC / MXene@MoS2 composite aerogel is obtained. In the present invention, the mass ratio of ammonium molybdate tetrahydrate, thiourea and water is preferably 1.0595:2.2835:30. In the present invention, the volume of the mixed solution and the number of BC / MXene aerogels are preferably 30mL:1. In the present invention, the soaking time is preferably 12h. In the present invention, the conditions of the hydrothermal reaction preferably include: a temperature of 200°C and a time of 18 to 24h. In the present invention, after the hydrothermal reaction, the BC / MXene@MoS2 composite aerogel is preferably obtained by washing three times with deionized water and anhydrous ethanol, and then vacuum drying at 60°C for 12h.
[0023] The present invention also provides the use of the BC / MXene@MoS2 composite aerogel described in the above technical solution in the preparation of electromagnetic wave absorbing materials.
[0024] The present invention also provides the use of the BC / MXene@MoS2 composite aerogel described in the above technical solution in improving the wave absorbing performance of electromagnetic wave absorbing materials.
[0025] The present invention also provides the application of the BC / MXene@MoS2 composite aerogel described in the above technical solution in improving the impedance matching of electromagnetic wave absorbing materials.
[0026] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0027] Example 1: In this example, a BC / MXene@MoS2 composite aerogel microwave absorbing material is prepared. The specific implementation steps are as follows: S1: Weigh 80 mg of monolayer MXene powder and 10 g of BC dispersion (0.8%wt) in a mass ratio of 1:1, add the MXene powder to the BC dispersion, stir for 5 h at room temperature with a magnetic stirring speed of 1300 r / min, and obtain a BC / MXene precursor dispersion with uniform composition; S2: Pour 10 ml of the BC / MXene precursor dispersion prepared in step S1 into a directional cold casting mold for freeze casting. The liquid nitrogen used for freeze casting has a freeze casting temperature range of -196°C and a freeze casting time of 1 hour. The product obtained after freeze casting is placed in a freeze dryer for freeze drying. The freeze drying temperature can be -55°C and the freeze drying time is 48 hours. After freeze drying, BC / MXene aerogel is obtained.
[0028] In this embodiment, the directional freezing casting mold includes two parts: a copper base and an acrylic square tube. The size of the copper base is 60×60×2mm, the wall thickness of the acrylic square tube is 5mm, and the inner cavity size is 20×20×25mm.
[0029] S3: The BC / MXene aerogel prepared in S2 is subjected to a hydrothermal reaction to grow MoS2 nanosheets on the aerogel surface. The specific steps of the hydrothermal reaction are as follows: 1.0595 g H 24 Mo7N6O 24 4H2O and 2.2835g CH4N2S were dissolved in 30ml deionized water, transferred to a 50ml hydrothermal reactor, and the BC / MXene aerogel was immersed in it for 12h, and then hydrothermally reacted at 200℃ for 18h. After the reaction, it was washed three times with deionized water and ethanol, and vacuum dried in a vacuum oven at 60℃ for 12h to obtain a BC / MXene@MoS2 composite aerogel microwave absorbing material with a size of 2×2cm in length and width and a thickness of 2.5mm.
[0030] S4: Prepare the BC / MXene@MoS2 composite aerogel; mix epoxy resin E-51 and m-phenylenediamine in a mass ratio of 5:1, and pour them into the BC / MXene@MoS2 composite aerogel (the composite aerogel is placed in a beaker with a bottom diameter of about 10 cm, and then the mixed solution is added thereto until the composite aerogel is completely covered), solidify under vacuum conditions, obtain the sample, cut the coaxial ring, and test its wave absorbing performance.
[0031] like Figure 1 As shown, the XRD spectrum of the BC / MXene@MoS2 composite aerogel microwave absorbing material in specific example 1 indicates that the material was successfully prepared.
[0032] like Figure 2 As shown in (a), it is the SEM image of the BC / MXene@MoS2 composite aerogel microwave absorbing material in Example 1. The results show that the prepared aerogel has an oriented structure and MoS2 nanosheets are evenly distributed on it.
[0033] like Figure 3The reflection loss curve of the BC / MXene@MoS2 composite aerogel microwave absorbing material at different thicknesses in Example 1 is shown; the results show that when the thickness is 2.55mm, the absorption bandwidth of the composite aerogel reaches an astonishing 7.04GHz, and when the thickness is 2.62mm, the minimum reflection loss reaches 52dB, indicating that the material has excellent absorbing performance and meets broadband absorption. And through subsequent measurements, the filler ratio of aerogel in epoxy resin is 5%wt. Overall, the absorbing material is very consistent with the current application requirements of lightweight, thin thickness, strong absorption, and wide bandwidth for the development of new microwave absorbing materials.
[0034] Example 2: This example adopts the same preparation method as Example 1, but the difference from the example is that in step S1, the amount of MXene powder added is 60 mg, and the rest is the same as Example 1, specifically as follows: S1: Weigh 60 mg of monolayer MXene powder and 10 g of BC dispersion (0.8%wt) in a mass ratio of 3:4, add the MXene powder to the BC dispersion, stir for 5 h at room temperature with a magnetic stirring speed of 1300 r / min, and obtain a BC / MXene precursor dispersion with uniform composition; S2: Pour 10 ml of the BC / MXene precursor dispersion prepared in step S1 into a directional cold casting mold for freeze casting. The liquid nitrogen used for freeze casting has a freeze casting temperature range of -196°C and a freeze casting time of 1 hour. The product obtained after freeze casting is placed in a freeze dryer for freeze drying. The freeze drying temperature can be -55°C and the freeze drying time is 48 hours. After freeze drying, BC / MXene aerogel is obtained.
[0035] S3: The BC / MXene aerogel prepared in S2 is subjected to a hydrothermal reaction to grow MoS2 nanosheets on the aerogel surface. The specific steps of the hydrothermal reaction are as follows: 1.0595 g H 24 Mo7N6O 24 4H2O and 2.2835g CH4N2S were dissolved in 30ml deionized water, transferred to a 50ml hydrothermal reactor, and the BC / MXene aerogel was immersed in it for 12h, and then hydrothermally reacted at 200℃ for 18h. After the reaction, it was washed three times with deionized water and ethanol, and vacuum dried in a vacuum oven at 60℃ for 12h to obtain a BC / MXene@MoS2 composite aerogel microwave absorbing material with a size of 2×2cm in length and width and a thickness of 2.5mm.
[0036] S4: Prepare the BC / MXene@MoS2 composite aerogel; mix epoxy resin E-51 and m-phenylenediamine in a mass ratio of 5:1, and pour them into the BC / MXene@MoS2 composite aerogel (the composite aerogel is placed in a beaker with a bottom diameter of about 10 cm, and then the mixed solution is added thereto until the composite aerogel is completely covered), solidify under vacuum conditions, obtain the sample, cut the coaxial ring, and test its wave absorbing performance.
[0037] The results show that, although the absorbing material prepared in this embodiment is also within the effective performance range, the absorption bandwidth is slightly reduced, and the absorption band is only 5.0 GHz.
[0038] Example 3: This example adopts the same preparation method as Example 1, but the difference from Example 1 is that in step S2, the cold source used is a low-temperature constant temperature reaction bath, the cold casting temperature is -80°C, and the rest is the same as Example 1; the details are as follows: S1: Weigh 80 mg of monolayer MXene powder and 10 g of BC dispersion (0.8%wt) in a mass ratio of 1:1, add the MXene powder to the BC dispersion, stir for 5 h at room temperature with a magnetic stirring speed of 1300 r / min, and obtain a BC / MXene precursor dispersion with uniform composition; S2: Pour 10 ml of the BC / MXene precursor dispersion prepared in step S1 into a directional cold casting mold for freeze casting. The low-temperature constant temperature reaction bath used for freeze casting has a freeze casting temperature range of -80°C and a freeze casting time of 1 hour. The product obtained after freeze casting is placed in a freeze dryer for freeze drying. The freeze drying temperature can be -55°C and the freeze drying time is 48 hours. After freeze drying, BC / MXene aerogel is obtained.
[0039] S3: The BC / MXene aerogel prepared in S2 is subjected to a hydrothermal reaction to grow MoS2 nanosheets on the aerogel surface. The specific steps of the hydrothermal reaction are as follows: 1.0595 g H 24 Mo7N6O 24 4H2O and 2.2835g CH4N2S were dissolved in 30ml deionized water, transferred to a 50ml hydrothermal reactor, and the BC / MXene aerogel was immersed in it for 12h, and then hydrothermally reacted at 200℃ for 18h. After the reaction, it was washed three times with deionized water and ethanol, and vacuum dried in a vacuum oven at 60℃ for 12h to obtain a BC / MXene@MoS2 composite aerogel microwave absorbing material with a size of 2×2cm in length and width and a thickness of 2.5mm.
[0040] S4: Prepare the BC / MXene@MoS2 composite aerogel; mix epoxy resin E-51 and m-phenylenediamine in a mass ratio of 5:1, and pour them into the BC / MXene@MoS2 composite aerogel (the composite aerogel is placed in a beaker with a bottom diameter of about 10 cm, and then the mixed solution is added thereto until the composite aerogel is completely covered), solidify under vacuum conditions, obtain the sample, cut the coaxial ring, and test its wave absorbing performance.
[0041] The results show that although the absorbing material prepared in this embodiment is also within the effective performance range, the pore size of the pore structure is slightly larger than that of the absorbing material prepared in Example 1. The pore size of the aerogel obtained by using liquid nitrogen as a cold source is about 20µm, while the pore size using a low temperature constant temperature reaction bath as a cold source is about 25-30µm.
[0042] Example 4: This example adopts the same preparation method as Example 1, but the difference from Example 1 is that the time of the hydrothermal reaction in S3 is 24 hours, and the rest is the same as Example 1.
[0043] S1: Weigh 80 mg of monolayer MXene powder and 10 g of BC dispersion (0.8%wt) in a mass ratio of 1:1, add the MXene powder to the BC dispersion, stir for 5 h at room temperature with a magnetic stirring speed of 1300 r / min, and obtain a BC / MXene precursor dispersion with uniform composition; S2: Pour 10 ml of the BC / MXene precursor dispersion prepared in step S1 into a directional cold casting mold for freeze casting. The liquid nitrogen used for freeze casting has a freeze casting temperature range of -196°C and a freeze casting time of 1 hour. The product obtained after freeze casting is placed in a freeze dryer for freeze drying. The freeze drying temperature can be -55°C and the freeze drying time is 48 hours. After freeze drying, BC / MXene aerogel is obtained.
[0044] S3: The BC / MXene aerogel prepared in S2 is subjected to a hydrothermal reaction to grow MoS2 nanosheets on the aerogel surface. The specific steps of the hydrothermal reaction are as follows: 1.0595 g H 24 Mo7N6O 24 4H2O and 2.2835g CH4N2S were dissolved in 30ml deionized water, transferred to a 50ml hydrothermal reactor, and the BC / MXene aerogel was immersed in it for 12h, and then hydrothermally reacted at 200℃ for 24h. After the reaction, it was washed three times with deionized water and ethanol, and vacuum dried in a vacuum oven at 60℃ for 12h to obtain a BC / MXene@MoS2 composite aerogel microwave absorbing material with a size of 2×2cm in length and width and a thickness of 2.5mm.
[0045] S4: Prepare the BC / MXene@MoS2 composite aerogel; mix epoxy resin E-51 and m-phenylenediamine in a mass ratio of 5:1, and pour them into the BC / MXene@MoS2 composite aerogel (the composite aerogel is placed in a beaker with a bottom diameter of about 10 cm, and then the mixed solution is added thereto until the composite aerogel is completely covered), solidify under vacuum conditions, obtain the sample, cut the coaxial ring, and test its wave absorbing performance.
[0046] The results show that the absorbing performance of the absorbing material prepared in this embodiment is also within the effective performance range, but compared with Example 1, Figure 2 The MoS2 nanosheets on the surface of the sample obtained in this embodiment are more abundant and uniform.
[0047] By comparing and analyzing the reflection loss curves of the BC / MXene@MoS2 composite aerogels prepared in Example 1, Example 2, Example 3 and Example 4, the wave absorption performance of the BC / MXene@MoS2 prepared in Example 1, Example 2, Example 3 and Example 4 was explored. The results are shown in FIG. Figure 4 As shown, compared with Example 2, Example 3 and Example 4, the BC / MXene@MoS2 prepared in Example 1 has significantly improved microwave absorption performance, indicating that multi-scale structural regulation is of great significance for optimizing the microwave absorption performance of materials.
[0048] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A BC / MXene@MoS 2 Composite aerogel, It is characterized in that Including BC / MXene skeleton and MoS loaded on BC / MXene skeleton 2 Nanosheets.
2. A BC / MXene@MoS according to claim 1 2 Preparation method of composite aerogel, It is characterized in that The following steps are involved: 1) Mixing the monolayer MXene powder with the bacterial cellulose dispersion to obtain a precursor dispersion; 2) freeze-casting the precursor dispersion obtained in step 1), and freeze-drying to obtain BC / MXene aerogel; 3) ammonium molybdate tetrahydrate, thiourea and water are mixed to obtain a mixed solution, and the BC / MXene aerogel obtained in step 2) is immersed in the mixed solution to obtain BC / MXene@MoS after a hydrothermal reaction. 2 Composite aerogel.
3. The preparation method according to claim 2, It is characterized in that In the step 1), the mass ratio of the monolayer MXene powder to the bacterial cellulose dispersion is 0.06-0.08:10; The mass percentage of the bacterial cellulose dispersion is 0.8%; The mixing is performed under stirring, and the stirring conditions include: a rotation speed of 1300 rpm and a time of 5 hours.
4. The preparation method according to claim 2, It is characterized in that The conditions of the freeze casting in step 2) include: a temperature of -80 to -196°C and a time of 1 hour; The freeze-drying conditions include: temperature of -55°C and time of 48h.
5. The preparation method according to claim 2, It is characterized in that In the step 2), the precursor dispersion is freeze-casted in a directional freeze-casting mold, wherein the directional freeze-casting mold comprises a copper base and an acrylic square tube. The size of the copper base is 60×60×2 mm, the wall thickness of the acrylic square tube is 5 mm, and the inner cavity size is 20×20×25 mm.
6. The preparation method according to claim 2, It is characterized in that In step 3), the mass ratio of ammonium molybdate tetrahydrate, thiourea and water is 1.0595:2.2835:30; The ratio of the volume of the mixed liquid to the number of BC / MXene aerogels is 30 mL:
1.
7. The preparation method according to claim 2, It is characterized in that The soaking time in step 3) is 12 hours; The conditions of the hydrothermal reaction include: temperature of 200° C. and time of 18 to 24 hours.
8. BC / MXene@MoS according to claim 1 2 Application of composite aerogels in the preparation of electromagnetic wave absorbing materials.
9. BC / MXene@MoS according to claim 1 2 Application of composite aerogel in improving the absorbing performance of electromagnetic wave absorbing materials.
10. BC / MXene@MoS according to claim 1 2 Application of composite aerogels in improving impedance matching of electromagnetic wave absorbing materials.
Citation Information
Patent Citations
Preparation method of molybdenum disulfide / MXene layered composite wave-absorbing material
CN107660114A
Carbon-based composite material based on expanded graphite as well as preparation method and application of carbon-based composite material
CN113264556A
MoS2 / MXene composite aerogel wave-absorbing material and preparation method thereof
CN113316378A
MXene-molybdenum disulfide-carbon nanofiber hybrid aerogel, epoxy resin-based composite material and preparation method of MXene-molybdenum disulfide-carbon nanofiber hybrid aerogel and epoxy resin-based composite material
CN115785528A
MoS2 / Ti2CTx MXene composite wave-absorbing material and preparation method thereof
CN116656317A
